наименьшее 28 наибольшее
Пошаговое объяснение:
f(x)=4x²+3x+6 на [-2;2]
f'(x)=(4x²+3x+6)'=8x+3
8x+3=0
8x=-3
x=-3/8∈[-2;2]
f(-2)=4*(-2)²+3*(-2)+6=4*4-6+6=16
f(-3/8)=4*(-3/8)²+3*(-3/8)+6=4*9/64-9/8+6=36/64-9/8+6=9/8+6= +6= наименьшее
f(2)=4*(2)²+3*2+6=4*4+6+6=16+12=28 наибольшее
наименьшее 28 наибольшее
Пошаговое объяснение:
f(x)=4x²+3x+6 на [-2;2]
f'(x)=(4x²+3x+6)'=8x+3
8x+3=0
8x=-3
x=-3/8∈[-2;2]
f(-2)=4*(-2)²+3*(-2)+6=4*4-6+6=16
f(-3/8)=4*(-3/8)²+3*(-3/8)+6=4*9/64-9/8+6=36/64-9/8+6=9/8+6= +6= наименьшее
f(2)=4*(2)²+3*2+6=4*4+6+6=16+12=28 наибольшее